Pseudoprogression after glioma therapy: a comprehensive review. (April 2013) - Kruser, Tim J; Mehta, Minesh P; Robins, H Ian
Over the last decade, pseudoprogression as a clinically significant entity affecting both glioma patient management and the conduct of clinical trials has been recognized as a significant issue. The authors have summarized the literature relative to the incidence, chronological sequence, therapy-relatedness, impact of O -6-methylguanine-DNA methyltransferase methylation status and clinical features of pseudoprogression. Evidence regarding numerous neuroradiologic techniques to differentiate pseudoprogression from tumor recurrence is summarized. The implications of pseudoprogression on prognosis and clinical trial design are substantial, and are reviewed. Relative to this, the overlapping terms pseudoprogression and radiation necrosis are clarified to produce an appropriate basis for future consideration and research regarding this important biological phenomenon.